Hyperactivation of NF-κB via the MEK signaling is indispensable for the inhibitory effect of cAMP on DNA damage-induced cell death - Blomhoff Heidi K; Carlsen Harald; Naderi Elin H; Kloster Martine M; Naderi Soheil (Molecular Cancer, 2011)
Abstract With cAMP signaling having a profound inhibitory effect on DNA damage-induced apoptosis in B-cell precursor acute lymphoblastic leukemia (BCP-ALL) cells, understanding how this signaling pathway affects the survival capacity of the cell has important implications for cancer therapy. We have recently shown that p53 is critical for the inhibitory effect of cAMP on genotoxic agents-mediated apoptosis in BCP-ALLs. Here, we show that elevation of cAMP levels in cells exposed to DNA damage enhances the nuclear translocation and DNA binding of NF-κB by accelerating the phosphorylation of IKKβ and thereby phosphorylation and degradation of IκBα. Furthermore, we show that the ability of cAMP to potentiate the ionizing radiation-induced activation of NF-κB requires the activity of MEK. Importantly, pharmacological or genetic ablation of NF-κB reversed the inhibitory effect of cAMP on DNA damage-induced apoptosis, demonstrating that, in addition to p53, cAMP relies on the activity of NF-κB to provide cells with a survival advantage in the face of DNA damage. Collectively, our results uncover a novel and important interaction between the cAMP and NF-κB pathways that may have implications for the targeted treatment of lymphoid malignancies, such as BCP-ALL, in which aberrant NF-κB activity functions as a driving force for treatment resistance.